(Enantio)selective Hydrogen Autotransfer: Ruthenium‐Catalyzed Synthesis of Oxazolidin‐2‐ones from Urea and Diols. (13th April 2016) - Peña‐López, Miguel; Neumann, Helfried; Beller, Matthias
Abstract: A novel strategy for the synthesis of oxazolidin‐2‐ones from vicinal diols and urea is described. In this heterocycle synthesis, two different C−O and C−N bonds are sequentially formed in a domino process consisting of nucleophilic substitution and alcohol amination. The use of readily available starting materials and the good atom economy render this process environmentally benign. While this transformation is already highly chemo‐ and regioselective, we also developed the first asymmetric version of this method using ( R )‐(+)‐MeO‐BIPHEP as the chiral ligand.